2004
DOI: 10.1016/s1090-3801(03)00065-x
|View full text |Cite
|
Sign up to set email alerts
|

The tridimensional personality theory and pain: harm avoidance and reward dependence traits correlate with pain perception in healthy volunteers

Abstract: The aim of the present study was to examine the possible role of personality traits in determining the variability of pain perception among individuals. More specifically, it was intended to test whether or not the three personality dimensions suggested by Cloninger in 1987 - mainly harm avoidance (HA), but also reward dependence (RD), and novelty seeking (NS), can predict interpersonal differences in responsiveness to experimental pain. Seventy healthy volunteers participated in the study. Their personality t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 53 publications
6
67
2
Order By: Relevance
“…On the other hand the higher scores of HA in patients with acquired pain, such as radiculopathies, neuropathies and osteoarthritis, raise the possibility of developing this personality profile in acquired conditions also, and not only genetically related, as some authors have suggested [46]. In keeping with our results, Pud et al [47] showed a correlation between high scores of HA with pain threshold (latency to pain onset), pain magnitude (VAS), and pain tolerance (time to withdrawal) using the cold pressor test in healthy patients. The involvement of serotonin in chronic pain [48][49][50][51] is consistent with the proposed physiopathological mechanisms of HA in the central nervous system [23].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand the higher scores of HA in patients with acquired pain, such as radiculopathies, neuropathies and osteoarthritis, raise the possibility of developing this personality profile in acquired conditions also, and not only genetically related, as some authors have suggested [46]. In keeping with our results, Pud et al [47] showed a correlation between high scores of HA with pain threshold (latency to pain onset), pain magnitude (VAS), and pain tolerance (time to withdrawal) using the cold pressor test in healthy patients. The involvement of serotonin in chronic pain [48][49][50][51] is consistent with the proposed physiopathological mechanisms of HA in the central nervous system [23].…”
Section: Discussionsupporting
confidence: 92%
“…During the last decade, several studies have applied Cloninger's theory to the area of pain perception in healthy subjects as well as to various clinical pain conditions. We have previously demonstrated that a high HA level was the major trait determining heightened cold pain perception in healthy volunteers [6]. Even more so, in that previous study we also found that individuals with a high score of HA in combination with a low score of RD appear to be the most sensitive to pain, whereas those with a low score of HA and a low score of RD appear to be the least sensitive to pain.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, there was an attempt to determine if the subjects in these subgroups differed in their Cloninger's three dimensions of personality scores [18] (i.e., outcome measure). Given the complexity of the pain experience and the associations found with personality traits in previous research [6] we deemed it worthwhile to further explore this issue in an attempt to strengthen earlier findings.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Besides, reward dependence, novelty seeking, and harm avoidance have been associated with the anxiety trait of patients with chronic pain. Moreover, cooperativity and self-transcendence are directly or indirectly associated with coping [7][8][9][10][11][12] . The Temperament and Character Inventory (TCI) is an international instrument to evaluate personality, validated to the Portuguese Language 13 .…”
Section: Introductionmentioning
confidence: 99%